Sexual and reproductive rights in Peru, beyond the Bicentenary - Távara Orozco, Luis (2021)
Objective: To clarify the concept of sexual and reproductive health, to situate it withinHuman Rights and, as a consequence, within Sexual and Reproductive Rights; todiscuss some gender issues; to examine the situation of sexual and reproductiverights in our country and what we expect for the years to come. Methodology:Review of the national medical literature in relation to sexual and reproductive rightsand systematize the information. Results: In the various components of sexual andreproductive health there are important deficiencies that need to be overcome inorder to achieve the well-being indicated by the Sustainable Development Goals.Conclusion: There is still much to be developed in the recognition of sexual andreproductive rights, appealing to the best performance and commitment of healthprofessionals.